Catalisadores nanoestruturados contendo ligas de 'PT' e 'TI''O IND.2' para a oxidação eletroquímica de etanol - Freitas, Fernanda Gabriel de [UNESP] (2014)
In this work, the influence of the addition of TiO2 on the catalytic activity toward ethanol oxidation reaction on PtRu and PtSn nanocatalysts was studied. The effect of the amount of TiO2 added was also investigated for the PtSn bimetallic catalysts. The studies were comparatively performed for carbon-supported catalysts with the same metallic component (Pt, PtRu or PtSn) with and without modification with TiO2. The synthesis of PtRu and PtSn nanoparticles with nominal composition equal to 50:50 and 70:30 (in atoms), respectively, was carried out by a modified polyol method, while TiO2 was synthesized separately by a sol-gel process. In order to evaluate the differences in the catalytic activity promoted by the presence of the oxide, while maintaining the same properties of the metallic part, the colloid of nanoparticles was separated into fractions: one was used to prepare the catalyst without oxide and the others were used for preparation of the TiO2 containing materials. Nanocatalysts were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and in situ X-ray absorption spectroscopy (XAS). The general electrochemical behavior was evaluated by cyclic voltammetry in acidic or alkaline solution and the electrocatalytic activity for ethanol oxidation was studied by potential sweeps and chronoamperometry. Overall, the results show that the presence of TiO2 enhances the catalytic activity for ethanol oxidation in acid medium in the low potential region, because of the changes in the Pt 5d band vacancy promoted by metal-oxide interactions. The studies involving the variation of the amount of TiO2 showed that the effects of oxide content are significant both in acidic and in alkaline medium. Experiments using in situ Fourier transform infrared reflection-absorption spectroscopy (FTIRAS) were performed in order to analyze qualitatively the products of alcohol oxidation at each...